Efficacy and safety of pirfenidone in the treatment of idiopathic pulmonary fibrosis patients: a systematic review and meta-analysis of randomised controlled trials - Wenjuan Wu; Guojun Zhang; Lingxiao Qiu; Jizhen Wu; Xueya Liu (BMJ Open)
Objectives Idiopathic pulmonary fibrosis (IPF) has been defined as a distinctive type of chronic fibrotic disease, characterised by a progressive decline in lung function and a common histological pattern of interstitial pneumonia. To analyse the efficacy and safety of pirfenidone in the treatment of IPF, a systematic review and meta-analysis was performed.Design This is a meta-analysis study.Participants Patients were diagnosed as IPF.Interventions Use of pirfenidone.Primary and secondary outcome Progression-free survival (PFS), acute exacerbation and worsening of IPF and Impact on adverse events.Measures The inverse variance method for the random-effects model was used to summarise the dichotomous outcomes, risk ratios and 95% CIs.Results A total of 9 randomised controlled trials with 1011 participants receiving pirfenidone and 912 controls receiving placebo were summarised. The pooled result suggested a statistically significant difference inall-cause mortality after pirfenidone use, with a summarised relative ratio of 0.51 (p<0.01). Longer PFS was observed in patients receiving pirfenidone compared with those who were given placebo (p<0.01). The IPF groups presented a high incidence of adverse events with a pooled relative ratio of 3.89 (p<0.01).Conclusions Pirfenidone can provide survival benefit for patients with IPF. Pirfenidone treatment was also associated with a longer PFS, a lower incidence of acute exacerbation and worsening of IPF.